Helminth contamination of Wild Ruminants in the West kazakhstan Region and activity of the supramolecular complex of albendazole with Polyvinylpyrrolidone at helminthoses - R. S. Karmaliyev; I. A. Arkhipov; B. M. Sidikhov; Zh. T. Usenov; B. O. Ertleuova; D. E. Gabdullin (Российский паразитологический журнал, 2020)
The purpose of the research is to establish the species composition and contamination of saigas with the main helminths, as well as to determine the effectiveness of the supramolecular complex of albendazole with polyvinylpyrrolidone at helminthoses in the conditions of the West Kazakhstan region. Materials and methods. Incomplete helminthological autopsy according to K. I. Skryabin was used to study the contamination of saigas with helminths. Supramolecular complex of albendazole with polyvinylpyrrolidone was tested on 30 saigas spontaneously infected with gastrointestinal strongylates and Moniezia spp. Animals of different groups of 10 animals each were administered orally the supramolecular complex of albendazole with polyvinylpyrrolidone at a single dose of 2.0 mg/kg of the AS compared with the base drug albendazole in a dose of 7.5 mg/kg of the AS. The control was a group of saigas that did not receive the drug. The effectiveness of the drugs was considered according to the data of coproovoscopic studies of saigas by the flotation method before and 14 days after administration. Results and discussion. The prevalence of saiga infection with Moniezia spp. in the West Kazakhstan region averaged 37%, Echinococcus sp. 25, Trychostrongilus spp. 62, Ostertagia spp. 87, Marshallagia sp. 87, Haemonchus sp. 75, Nematodirus spp. 87 and Trichocephalus spp. 25%. The 100 % efficiency of the supramolecular complex of albendazole with polyvinylpyrrolidone was obtained at strongylatosis of the gastrointestinal tract and monieziosis of saigas at a dose of 2.0 mg/kg of the AS according to the studies of fecal samples with 80–70% effectiveness of the base drug.